Adam SPGD algorithm in freeform surface in-process interferometry - Wu, Jinling; Hu, Chengwen; Liu, Renhu; Wu, Shengyang; Cao, Jiaquan; Cheng, Zhongtao; Yu, Benli; Zhang, Lei (Optics express, 2022)
The adaptive interferometer has been recently proposed to realize the metrology of unknown freeform surfaces with several restructured algorithms for feedback control. The adaptive moment estimation (Adam) stochastic parallel gradient descent (SPGD) algorithm is employed in this paper for fringes release. The proposed algorithm makes considerable progress in relieving conflict of the convergence rate, speed, and parameters intervention. Simulations and experiments show its 37% time saving and 99% convergence rate, with arbitrarily configured parameter increment, compared with the SPGD algorithm. It would have great potential in in-process tests in freeform surface fabrication or large-volume testing.